Analysis of the Influence of MVA, EVA, and FVA on Stock Returns in Coal Mining Companies Listed on the Indonesia Stock Exchange for the Period 2018-2023 (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study examines the impact of Market Value Added (MVA), Economic Value Added (EVA), and Financial Value Added (FVA) on stock returns in energy-sector mining companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. A quantitative approach with multiple linear regression was applied to 23 purposively selected firms based on data availability. Secondary data were obtained from annual reports and stock prices published on the IDX website. The findings show that EVA has a significant effect on stock returns (p = 0.048 < 0.05), while MVA (0.075) and FVA (0.080) are not significant individually. However, the three variables collectively influence stock returns (p = 0.031 < 0.05). The adjusted R² of 0.396 indicates that 39.6% of return variability is explained by the model, with the rest influenced by other factors. Overall, EVA emerges as the key indicator for investors in evaluating return potential, while market-based measures such as MVA are less decisive, and historical value indicators (FVA) are less statistically relevant as predictors of stock returns. From a managerial perspective, firms are encouraged to focus on capital efficiency and sustainable economic value creation to enhance their investment appeal.